Questionnaire based assessment of awareness about infection control practices regarding COVID-19 among health care workers - Mane, Abhijeet K.; Tolpadi, Anuradha G.; Modak, Meera S.; Verma, Ashok K.; Achenkunju, Ancy C.; Wadghare, Usha; Shankar, Radhika (International Journal of Advances in Medicine, 2021)
Background: Healthcare workers (HCWs) are at frontline of response of the current pandemic of the COVID-19. This exposes them to risk of infection due to insufficient knowledge and unhealthy practices. The aim of the study was to assess the knowledge of infection control practices among HCWs regarding COVID-19. Methods: A web-based cross-sectional survey was conducted between April 2020 and June 2020. A 21-questions survey was developed and distributed among study population. A total of 622 HCWs working in a dedicated COVID-19 hospital participated in this study. Descriptive statistics was applied to represent participant characteristics and Chi-square test was used to evaluate the level of association among variables with a significance level of <0.05. Results: Out of 622 participants, 443 (71.22%) were females and 179 (28.78%) were males. Majority of the participants were nurses 308 (49.5%) followed by resident doctors 152 (24.4%), faculty doctors 108 (17.3%) and ancillary staff 54 (8.6%). Most participants 424 (68.1%) were less than 30 years of age. The overall response to survey was satisfactory with average correct responses recorded at 70.9%. Faculty doctors and resident doctors scored maximum average of 73% marks. Conclusions: The study participants showed sufficient basic knowledge about infection control practices regarding COVID-19. It also highlights the importance of continued training and educational interventions which are required to battle the present pandemic situation.